Research on Improving the Working Current of NbOx-Based Selector by Inserting a Ti Layer - Liu, Chunlei; Ma, Guokun; Zeng, Junpeng; Tan, Qiuyang; Zhang, Ziqi; Chen, Ao; Liu, Nengfan; Wan, Houzhao; Wang, Baoyuan; Tao, Li; Rao, Yiheng; Shen, Liangping; et al. (Frontiers in Materials, 2021)
To achieve the highest possible integration storage density in the V-point structure, the working current of the selector in the one-selection one-resistance (1S1R) structure should match with the resistance random access memory (RRAM). In this study, a selector device is designed with a Ti/NbOx/Ti/Pt structure through the magnetron sputtering method and achieves excellent performance of threshold switching under ultra-large compliance current (CC) up to 100 mA. Furthermore, both the switching voltages and the OFF-state resistance of the device demonstrate excellent stability even when CC is increased to a milliampere level, attributed from the existence of metallic NbO in the switching layer. This study provides evidence that a Ti/NbOx/Ti/Pt device has a great potential to drive RRAM in the V-point structure.